The role of GTP binding and hydrolysis at the atToc159 preprotein receptor during protein import into chloroplasts - Wang, Fei; Agne, Birgit; Kessler, Félix; Schnell, Danny J. (My University, 2008)
The majority of nucleus-encoded chloroplast proteins are targeted to the organelle by direct binding to two membrane-bound GTPase receptors, Toc34 and Toc159. The GTPase activities of the receptors are implicated in two key import activities, preprotein binding and driving membrane translocation, but their precise functions have not been defined. We use a combination of in vivo and in vitro approaches to study the role of the Toc159 receptor in the import reaction. We show that atToc159-A864R, a receptor with reduced GTPase activity, can fully complement a lethal insertion mutation in the ATTOC159 gene. Surprisingly, the atToc159-A864R receptor increases the rate of protein import relative to wild-type receptor in isolated chloroplasts by stabilizing the formation of a GTP-dependent preprotein binding intermediate. These data favor a model in which the atToc159 receptor acts as part of a GTP-regulated switch for preprotein recognition at the TOC translocon.